KEPUASAN MASYARAKAT DI MPP DEMAK DIPENGARUHI KUALITAS PELAYANAN, FASILITAS, DAN AKSESIBILITAS - Rihan Hafizni; Tossy Aryanto; Desyani Purwaningrum (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2026)
The Public Service Mall (MPP) launched by the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Demak Regency is an innovation aimed at simplifying public licensing and non-licensing services in the region. The purpose of this research is to analyze the influence of service quality, facilities, and accessibility on public satisfaction at the Public Service Mall (MPP) of Demak Regency. The population in this study consists of service users at the Public Service Mall (MPP) of Demak Regency during the period from January to July 2024, totaling 23,978 individuals. The sample for this study was selected using the purposive sampling method, resulting in a total of 100 respondents. The data analyzed are primary data collected through questionnaires. The data processing results include descriptive analysis, F-test results, coefficient of determination (R²) test results, and hypothesis testing results. The findings of this research indicate that: Service quality has a positive and significant effect, with a significance value of 0.028 (< 0.1). Facilities have no effect on public satisfaction, with a significance value of 0.557 (> 0.1). Accessibility has a positive and significant effect on public satisfaction, with a significance value of 0.000 (< 0.1). Recommendations include improving service quality to be more professional in enhancing public satisfaction at the Public Service Mall (MPP) of Demak Regency. Additionally, maintaining and completing deficient facilities is essential to simplify public services and increase satisfaction.